Policemen Assertiveness and Communication Style in a Pandemic Context - Rogoz, Simona (New Trends in Psychology, 2022)
During the evolution of human skills in various fields of activity, a series of changes that produced results where those directly involved became aware of their power of manifestation took place. Moreover, such aspects can be integrated in all fields of activity, if access to information with and about the benefits of conscious involvement and their constant implementation is facilitated. One of these aspects refers to the personal communication style.There were more than a few contexts in which a handful of people had the courage and power to change the course of implementation of some ideas in their field of activity (including certain legislative frameworks) by improving communication and making the transition from a passive or aggressive communication style to an assertive one. This implementation can be done in compliance with all the rules and procedures imposed by the legislative framework of a certain activity. This way, we can reach results that highlight the effectiveness of improving the communication style and its development towards an assertive one.